Dietary use of sex steroids and thyroid hormone as potential growth promoters for the spotted scat (Scatophagus argus Linnaeus) and mikfish (Chanos chanos Forskal) - Cruz, Paul Felipe S. (College of Fisheries, University of the Philippines in the Visayas, 1988)
The study evaluates the potential use of 17a-methyltestosterone (MT), estradiol-17B (E2), and/or 3,5,3 -tiido-L-thyronine (T3), as growth promtoers for the spotted scat Scatophague argus and milkfish Chanos chanos. Scat fry were fed indoor diets containing 0, 0.1, 1.0, 5.0, and 10.0 ppm T3. No effects on growth, feed efficiency, and survival was detected after 200 days. Increasing doses resulted to a decreasing trend in condition factor and body-tail ratio. Other banormalities were evident at 5.0 and 10.0 ppm T3. In adult scats, MT or E2 at 10.0 and 20.0 ppm, or 10.0 ppm combination with 5.0 ppm T3 failed to imrpove growth after 70 days in pond cages. All hormone treatmentrs had depressed growth and feed consumption. The control had the highest hepatososmatic index but was no significant to treatments 10.0 and 20.0 ppm E2. In milkfish, MT was tested ondoor on juveniles at 0, 1.0, 5.0, 10.0, 20.0, and 40.0 ppm. After 112 days, MT at 1.0 ppm appeared to be anabolic, improving growth by 27.1%. Higher doses tended to depress food consumption and growth. Growth was significantly depressed at 40.0 ppm MT. No hormonal effect was observed on feed efficiency and survival. Increasing MT doses caused a trend of increasing condition factor. There appears to be no anabolic potential of MT, E2, and/or T3 on scats. The study suggests species specificity on the anabolic potency of these hormones. Use of MT to enhance growth in juvenile milkfish appears to have promising commercial applications.